2014
DOI: 10.1111/add.12508
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and prospective relation of cannabis potency, dosing and smoking behaviour with cannabis dependence: an ecological study

Abstract: Cannabis users titrate their delta-9-tetrahydrocannabinol intake by inhaling lower volumes of smoke when smoking strong joints, but this does not fully compensate for the higher cannabis doses per joint when using strong cannabis. Thus, users of more potent cannabis are generally exposed to more delta-9-tetrahydrocannabinol. Smoking behaviour appears to be a stronger predictor for cannabis dependence severity than monthly delta-9-tetrahydrocannabinol dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
62
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 29 publications
4
62
1
1
Order By: Relevance
“…Van der Pol et al 's [1] findings, however, throw this into some doubt. To understand why there is a discrepancy here, and its import, it is essential to consider how cannabis exposure/dose is typically measured and, thereby, how past studies may have clouded our understanding of the association between cannabis use and dependence.…”
mentioning
confidence: 94%
See 4 more Smart Citations
“…Van der Pol et al 's [1] findings, however, throw this into some doubt. To understand why there is a discrepancy here, and its import, it is essential to consider how cannabis exposure/dose is typically measured and, thereby, how past studies may have clouded our understanding of the association between cannabis use and dependence.…”
mentioning
confidence: 94%
“…[3]); in comparison, van der Pol et al's participants were using cannabis ranging from 3.6 to 15.7% THC and they smoked it as per usual, such that their smoking topographies varied. Taken together with the finding that total number of puffs and puff volume were significant predictors of dependence in van der Pol et al's study, these differences throw at least some doubt on the 'real world' validity of findings from previous studies (whether using real or proxy measures of exposure/dose) and illustrate how important naturalistic studies are to increasing our understanding of the acute and long-term effects of cannabis use, including dependence.Of particular interest here is the 'typical' smoking topography that van der Pol et al [1] found was predictive of cannabis dependence. Taking more frequent puffs of greater volume when commencing a session is evocative of someone seeking a quick hit, such as to 'take the edge off', then smoking with less urgency as the desired effects kick in.…”
mentioning
confidence: 96%
See 3 more Smart Citations